The Use of Talking Chips Technique in Teaching Speaking - Ahmad Junaedi (ELITE JOURNAL, 2020)
This research aim to identify how the implementation of Talking Chips technique can improve the students’ speaking ability. The population is student of grade X SMAN 3 MAJENE. The sample of this study was only one class and total number of students was 30 students. Research method that used is quasi-experimental design. This study was conducted by using multiple pre-test and post-test. During the treatments, there were problems related to classroom management, fluency and comprehensibility. Those problems could be minimized. After posttest, there were still problems, but the problems were fewer than previous ones because students had showed the awareness in speaking English. The research findings show that the implementation of talking chips could improve the students’ speaking skill in delivering speech and the classroom situation of speaking class. The improvement of students speaking skill includes: 1) Students had enough vocabulary to deliver speech; 2) the students were able to pronounce the word correctly during delivering the speech; 3) the students could produce the sentences grammatically correct; 4) the students delivered the speech more fluent. The improvement of classroom situation includes: a) the class was more alive because the students’ participate actively during the speaking class; b) there was an equal participation during the speaking class; c) the students were motivated to speak English than Indonesian. It can be concluded that the implementation of talking chips can improve the students speaking ability in delivering speech and the classroom situation. It is hoped that this result can give other teachers inspiration to implement talking chips in their classroom.